Role of unsaturated hydrocarbon lubricant on the friction behavior of amorphous carbon films from reactive molecular dynamics study - Li, Xiaowei; Wang, Aiying; Lee, Kwang-Ryeol (ELSEVIER SCIENCE BV, 2019)
Compositing amorphous carbon (a-C) film with fluid lubricant could successfully improve the friction properties and prolong the service life and reliability of protected components. However, the inevitable existence of unsaturated molecules in base oil, especially its potential effect on the friction behavior and related mechanism are still not fully understood. In this paper, the friction behavior of amorphous carbon (a-C) composited with unsaturated hydrocarbon lubricant, C5H10 as one of linear alpha olefins (AO), was explored by reactive molecular dynamics simulation, and the role of C5H10 content on friction property and interfacial structure was mainly analyzed. Results revealed that at the fixed contact pressure, the unsaturated C5H10 bound with a-C in the form of weak intermolecular interactions rather than chemical bonding and there was also no C5H10 dissociation observed; the friction coefficient was strongly dependent on the small unsaturated hydrocarbon, which decreased obviously with C5H10 content. In particular, compared to the dry condition, the existence of C(5)H(1)0 molecules at the friction interface could significantly reduce the friction coefficient by 99.2% maximally. By the systematical analysis of interfacial hybridization structure and AO mobility, it indicated that the synergistic mechanism for the low friction originated from the self-passivation of a-C surface and AO hydrodynamic lubrication. Our results not only disclose the effect of unsaturated hydrocarbon molecules in bas oil on friction behavior and define the underlying lubrication mechanism, but also suggest a strategy for the design of both fluid lubricant and friction interface to realize the long-lifetime application.
Keywords: DIAMOND-LIKE CARBON; TOTAL-ENERGY CALCULATIONS; AB-INITIO; STRUCTURAL-PROPERTIES; SCALE TRIBOLOGY; MECHANISM; STRESS; TRANSFORMATION; SIMULATIONS; HYDROGEN